English

Factorise x3 + 6x2 + 11x + 6 completely using factor theorem. - Mathematics

Advertisements
Advertisements

Question

Factorise x3 + 6x2 + 11x + 6 completely using factor theorem. 

Sum

Solution

Let f(x) = x3 + 6x2 + 11x + 6

For x = –1

f(–1) = (–1)3 + 6(–1)2 + 11(–1) + 6

= –1 + 6 – 11 + 6

= 12 – 12

= 0

Hence, (x + 1) is a factor of f(x). 

             x2 + 5x + 6
`x + 1")"overline(x^3 + 6x^2 + 11x + 6)`
           x3 + x2                      
                5x2 + 11x
                5x2 + 5x               
                          6x + 6
                          6x + 6         
                             0
∴ x3 + 6x2 + 11x + 6 = (x + 1)(x2 + 5x + 6)

= (x + 1)(x2 + 2x + 3x + 6)

= (x + 1)[x(x + 2) + 3(x + 2)]

= (x + 1)(x + 2)(x + 3)

shaalaa.com
Factorising a Polynomial Completely After Obtaining One Factor by Factor Theorem
  Is there an error in this question or solution?
Chapter 8: Remainder and Factor Theorems - Exercise 8 (C) [Page 112]

APPEARS IN

Selina Mathematics [English] Class 10 ICSE
Chapter 8 Remainder and Factor Theorems
Exercise 8 (C) | Q 7 | Page 112
Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×